"How reliable an ally?": Surveying American power and credibility after the fall of Saigon—and Kabul. (March 2022) - McKercher, Asa
The withdrawal of US forces from Afghanistan, and the subsequent collapse of the Western-backed Afghan government in August 2021, raised doubts in the United States and abroad about the limits and credibility of American power. For some observers, the situation seemed to parallel the fall of the South Vietnamese regime in April 1975. Given the comparisons being drawn between Saigon and Kabul, this brief paper examines a series of Canadian diplomatic reports produced in the wake of the events in South Vietnam. Addressing the question of how reliable the United States was as an ally, the conclusions drawn in these reports should give some pause to doomsaying about US security commitments. Although the contemporary situation differs from that of the mid-1970s, Canadian observers recognized that American power rested on a firm foundation.